An Electrochemiluminesence Chiral Sensor for Propranolol Enantiomers Based on Functionalized Graphite‐like Carbon Nitride Nanosheets. Issue 1 (10th September 2019) - Zhu, Shu; Ran, Peiyao; Wu, Jingling; Chen, Min; Fu, Yingzi
Abstract: Graphite‐like carbon nitride nanosheets (g‐C3 N4 ) have been attracted considerable attention for their applications in catalysis and electrochemiluminesence (ECL) sensor. In this paper, a facile solvothermal method was employed to prepare the functionalized nanocomposites with metal salts cadmium carbonate (CdCO3 ) and g‐C3 N4 hybrids (g‐C3 N4 ‐CdCO3 ). The prepared materials were characterized by scanning electron microscope (SEM), X‐ray energy dispersive spectroscopy (EDX) and Fourier transform infrared spectra (FTIR). The nanocomposites was used not only as a new type luminophore but also as a chiral selector in this simple and sensitive ECL chiral sensor system for the recognition and detection of propranolol (Pro) enantiomers via quenching effect. The obvious difference of ECL signal of S‐Pro and R‐Pro was obtained. Thus, the sensor had the ability to distinguish Pro enantiomers. The mechanism of recognition was discussed by the theoretical calculation of binding constant and the water contact angle experiments. The sensor for Pro enantiomers was developed at wide concentration range from 0.001 to 1 mmol⋅L −1 . The sensor with excellent sensitivity, stability and reproducibility provide a new strategy based on ECL for chiral recognition and the ECL chiral sensor. Abstract :